Features of ultrastructural restructuring of hemocapillaries of the submandibular gland in rats in case of diabetes mellitus - Taras Kotyk (Kazimierz Wielki University, 2015)
Kotyk Taras. Features of ultrastructural restructuring of hemocapillaries of the submandibular gland in rats in case of diabetes mellitus. Journal of Education, Health and Sport. 2015;5(10):284-290. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33154 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A284-290 https://pbn.nauka.gov.pl/works/665698 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015.   Features of ultrastructural restructuring of hemocapillaries of the submandibular gland in rats in case of diabetes mellitus   Kotyk Taras     Department of Human Anatomy, Operative Surgery and Topographic Anatomy Ivano-Frankivsk National Medical University, Ivano-Frankivsk, Ukraine     Keywords: diabetes mellitus; submandibular gland; hemocapillaries.     Introduction. According to the International Diabetes Federation the number of patients with diabetes mellitus (DM) continues to grow rapidly. It has been established that already in the early stages of DM dysfunction of the vascular endothelium occurs leading to the development of diabetic microangiopathy that, in turn, results in dysfunction of salivary glands. The submandibular gland is considered to be the main source for basal secretion of saliva and its dysfunction in case of DM results in the development of xerostomia. However, the features of morphological changes of its hemocapillaries in this pathology have been insufficiently studied. The aim is to establish the features of ultrastructural restructuring of hemocapillaries of the submandibular gland in case of experimental DM. Materials and methods. In the Wistar rats DM was induced with streptozotocin (6 mg / g body weight). Submandibular gland's capillaries were investigated on the ultrastructural level and their morphometric parameters were measured. Results. During experiment were observed structural changes in the basement membrane and morphometrically its thickening was increasing. Since 42nd day destructive changes of endothelial cells have developed manifested, shape factor of the lumen of capillaries was decreasing that indicating pronounced diabetic microangiopathy of the submandibular gland. In later stages (56 - 70 days) destructive changes have increased, morphometrically were confirmed the thinning of transport area of endothelial cells and greater decreasing of shape factor of hemocapillaries lumen. Conclusions. Hemocapillaries of the submandibular gland are sensitive to pathogenetic factors developing in DM and dependent on its duration.